Fabrication and characterization of palm sugar tree (Arenga pinnata) fiber composites reinforced by polyester resin - Timbangen Sembiring; Evi Sitepu; Martha Rianna; Aditia Warman; Singarimbun; Perdinan Sinuhaji; Kerista Sebayang (Functional Materials, 2019)
Palm sugar tree (Arenga pinnata) fiber composites reinforced by polyester resin have been obtained and characterized as an alternative material for neutron beam shield. The content of sugar palm fiber was varied by 0, 5, 10, 15 and 20 % of volume fraction, which was strongly related to the physical and mechanical properties. The maximum value of mechanical properties of the composites was found to be at 10 %. The average results on chemical composition of sugar palm tree fiber showed cellulose, hemicelluloses, and lignin content of 47.8 %, 6.5 %, 22.3 %, respectively. As a result of neutron activation analysis, several elements were identified, such as Cl, Mn, K, Br, La, Cr, Fe, Hg, Sc and Zn, in the composite containing sugar palm fibers enforced by polyester resin. A possibility was studied to use this material for protection from thermal neutrons.The counts of neutron beams decreased as the content of sugar palm fibers increased. This fact implies that the composites containing sugar palm fibers can be used as shield materials for neutron beams.